(untitled) (Journal of Interdisciplinary Insights, 2025)
This study explores the application effect of Large Language Model (LLM) in the cultivation of English writing ability of students in traditional Chinese medicine((TCM) ) colleges and universities, with a focus on solving problems such as inaccurate expression of writing ability and weak genre awareness in traditional English writing teaching. The research constructed the subject English writing of students in TCM colleges and universities assisted by LLM, covering core links such as language expression, structure optimization and cross-cultural rhetorical adaptation, aiming to improve the accuracy, standardization and academic nature of students’ professional English writing. A total of 120 undergraduate students from a certain university of traditional Chinese medicine (with CET4 level in English, equivalent to CEFR B1-C1 level) were selected as the research subjects and divided into the experimental group (60 students, with LLM-assisted teaching) and the control group (60 students, with traditional teacher feedback teaching) for a 12-week comparative experiment. Through quantitative analysis and qualitative research, it is concluded that the writing ability of the students in the experimental group has significantly improved, especially in terms of writing expression ability and vocabulary application.